A organização dos espaços na educação infantil: possibilidades educativas na proposta Fazer em Cantos - Pessoa, Priscila Sales Rodrigues [UNESP] (2015)
The research entitled The organization of Spaces in Children's Education: educational possibilities in the proposal Doing in corners is connected to the Post Graduation Program in Education at the Sciences and Technology of the State University Julio de Mesquita Filho FCT / UNESP, in Presidente Prudente, São Paulo State, specifically for Childhood and Education. The goal of the research is school space. It has the general goal of investigating how the organization of classroom spaces shows the educational goals, actions, success and the difficulties of teachers. Professionals show dilemma and significant experiences, regarding space organization, which deserve investigation, in the sense of qualifying the help for the children. Our study starts from the consideration of space as a curricular element, of the importance of space organization of the children Educational Institutions, that meet the necessities of the children and favor their exploring action problematizing some questions: How are organized the spaces of the Childhood Education Spaces? What are the educational goals of teachers in the space organizations and display of materials? The project is characterized as a study case, in a qualitative approach. A bibliographic research about space organization in Children Education was performed highlighting learning corners, as well as the analysis of documents of official publication by the Education Derpartment talking about the topic. The theory referential in fundamented in books by Brazilian authors. Barbosa (2011) Hom (2011 e 2004), Campos (2005), Guimarães (2009) Krammer (2009), Faria (2009)...